1990
DOI: 10.1111/j.1600-0404.1990.tb04488.x
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potential (P300) in epilepsy

Abstract: The P300 component of auditory event-related potential was studied in 39 patients with temporal lobe epilepsy (TLE), 26 with idiopathic generalized epilepsy (IGE) and 28 controls. The age-corrected P300 latencies were significantly longer in TLE patients compared with those in IGE patients and controls. Neither the duration of epilepsy nor clinical manifestation was related to the P300 component in the same epileptic syndrome. The age-corrected P300 latencies recorded from Cz were significantly prolonged in TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 14 publications
3
29
1
Order By: Relevance
“…All the studies involving the auditory processing of epileptic patients were performed using auditory evoked responses. 28,29 The high prevalence of disorders reported in the literature when using the auditory processing paradigm through long latency potentials, in conjunction with our findings, suggests that epileptic patients may have sound processing deficits. Several authors, [31][32][33] in their studies with epileptic children, have reported on the importance of areas such as the hippocampus, thalamus, cortical-thalamic circuit, temporal lobe and auditory association cortex in sound processing.…”
Section: Discussionsupporting
confidence: 70%
“…All the studies involving the auditory processing of epileptic patients were performed using auditory evoked responses. 28,29 The high prevalence of disorders reported in the literature when using the auditory processing paradigm through long latency potentials, in conjunction with our findings, suggests that epileptic patients may have sound processing deficits. Several authors, [31][32][33] in their studies with epileptic children, have reported on the importance of areas such as the hippocampus, thalamus, cortical-thalamic circuit, temporal lobe and auditory association cortex in sound processing.…”
Section: Discussionsupporting
confidence: 70%
“…The analysis now, however, did not show a significant difference in P3 latencies and amplitudes between patients who did suffer from post-encephalitic epilepsy and those who did not. Other Studies of P3 characteristics in epilepsy describe increased latencies and greater amplitudes in epileptic subjects [22][23][24]. Again, one reason for the lack of statistically significant results is the small number of our study participants.…”
Section: In This Study Auditory Erps In 47 Patients Have Been Analyzcontrasting
confidence: 47%
“…First, steroid treatment (using adrenocorticotropic hormone and corticotropin-releasing hormone at low dose) did not alter ERP latencies in healthy adult controls 51,52. Second, in other severe epilepsies therapeutic doses of other anticonvulsants did not alter ERP latencies 47,53. We did not identify clear ERP differences in relation to clinical factors such as development before seizure onset, the presence of brain MRI abnormality, EEG background abnormality, and focal epileptiform activity, albeit limited by small sample size.…”
Section: Discussionmentioning
confidence: 98%